2022
DOI: 10.1186/s40824-022-00281-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of antibacterial nano-silver embedded bioactive hydrogel to repair infectious skin defects

Abstract: Background Hydrogels loaded with antimicrobial agents have been widely used for treating infected wound defects. However, hydrogels derived from a porcine dermal extracellular matrix (PADM), containing silver nanoparticles (AgNPs), have not yet been studied. Therefore, we investigated the therapeutic effect of an AgNP-impregnated PADM (AgNP–PADM) hydrogel on the treatment of infected wounds. Methods An AgNP–PADM hydrogel was synthesized by embeddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Similarly, the particles’ diameter found in GelMA matches the shape and size range of the originally characterised AgNPs pre-encapsulation. Similar results were reported where TEM images revealed that the 5 nm AgNP sizes were negligibly different before the AgNPs had been added to a porcine derived hydrogel; however, aggregation was detected with a bigger particle size of 50 nm [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, the particles’ diameter found in GelMA matches the shape and size range of the originally characterised AgNPs pre-encapsulation. Similar results were reported where TEM images revealed that the 5 nm AgNP sizes were negligibly different before the AgNPs had been added to a porcine derived hydrogel; however, aggregation was detected with a bigger particle size of 50 nm [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…AgNP-loaded CS-AA hydrogels revealed that the different sizes were compared with the pure AgNPs. As shown in Figure S1D, AgNPs in the CS-AA/AgNPs composite were found to have an average size of 60 nm ranging from 10 to 80 nm . These observations are mainly to the strong interaction between the AgNPs and CS-AA hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S1D, AgNPs in the CS-AA/AgNPs composite were found to have an average size of 60 nm ranging from 10 to 80 nm. 49 These observations are mainly to the strong interaction between the AgNPs and CS-AA hydrogels. It was expected that a homogeneous distribution of AgNPs would be achieved throughout the CS-AA hydrogels, although there was a quick reduction of the silver ions into the AgNPs.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Ag NPs porcine dermal decellularized extracellular matrix Ag NPs destroyed the structure of bacteria. [206] reduced graphene oxide (rGO) DA modified HA (DA-HA) High temperature (above 50°C) could kill bacteria through destroying some enzymes and proteins.…”
Section: Ag Nps Galacto-xyloglucan and Pammentioning
confidence: 99%